PROTECTION OF CHILDREN'S RIGHTS IN THE ASPECT OF INTERNATIONAL LAW - Ni Ketut Suriati (Ganesha Law Review, 2023)
This article aims to (1). Children and Child Protection in Indonesian Law. (2). How to Protect Children's Rights in Aspects of International Law. The results of the discussion of this article show that (1) In Law no. 23 of 2002 concerning the protection of children, states that children are a mandate and gift from God Almighty, in which the dignity and worth of being a complete human being is inherent in him. Guaranteed rights for children are protected through Law no. 34 of 2014, there are 4 general principles of child protection, namely the principle of non-discrimination, the principle of the best interests of the child, the principle of the right to life and the principle of respect for the opinion of children, the regulation regarding the protection of children's rights in Indonesia is also contained in the 1945 Constitution Article 28B Paragraph ( 2), as well as in Law no. 39 of 1999 concerning Human Rights, and Law no. 23 of 2002 concerning Child Protection. (2) The regulation regarding the protection of children's rights in the aspect of international law is contained in the Convention on the Rights of the Child which was declared unanimously on November 20, 1989 by the United Nations General Assembly (UN Resolution No. 44/25 dated December 5, 1989). -Children's rights are also contained in the ILO Conventions.